Response of sunflower cultivars to plant density in two planting dates. I. Grain and oil yield and yield component - Rizzardi, Mauro Antonio; da Silva, Paulo Regis Ferreira (Pesquisa Agropecuaria Brasileira, 1993)
Two experiments were conducted at Eldorado do Sul, Rio Grande do Sul, Brazil, in order to evaluate the plant density most adequate to obtain high grain and oil yield for different cultivars and to evaluate plant density effects in the grain yield components. In 1989/90, the cultivars tested were Conti 711, DK 180 and GR-10, planted on July 28 and September 18, under four plant densities 30, 50 70 and 90 thousand plants/ha. In 1990/91, the cultivars tested were GR-16 and GR-10, planted on July 26 and September 17, under four plant densities 30, 50, 70 and 90 thousand plants/ha. The results showed that the cultivars presented different densities to obtain the maximum grain and/or oil yield, regardless of planting date. In 1989/90, the short season cultivar with low height (Conti 711) presented higher oil yield potential in 90 thousand plants/ha. On the other hand, the long season cultivars with average and high height (DK 180 and GR-10, respectively) presented higher grain and oil yield potentials in 30 thousand plants/ha. In 1990/91, the cultivar low height (BR-16) presented higher grain and oil yield potential in 70 thousand plants/ha. On the other hand for grain and oil yield, the cultivar GR-10 was not affected by plant density, in function of the low grains yield. As density increased, the number of grain per head decreased more intensively in the cultivars with average and high height in contrast with the cultivars with low height. On the other hand for the other component, weight of 1,000 grains there was no interaction between cultivar and plant density. Oil content increased as density did only in the cultivar Conti 711.